SISTEM INFORMASI PENGELOLAAN STOK PERHIASAN EMAS DENGAN METODE LIFO PADA TOKO EMAS SENANG - Linda; Syafri Arief; Sudirman (STMIK KHARISMA Makassar, 2018)
This study aims to design a system that can help the Golden Store Happy to handle the management of gold jewelry stock, where the stock management using Last In First Out method. To obtain data and information that support the implementation of this research, conducted observations and interviews. Information Systems Stock control is designed using Data Flow Diagrams (DFD), then implemented using Visual Basic 6.0 and Microsoft Access programming as a data processor, then tested using black box testing method. With this new system is expected the owner of Golden Store Happy to run the process of stock management.